Early Outcome of Bifurcational Coronary Artery Stenting - Bedair, Ahmed Y.; Farhan, Hasan Ali; Jabir, Usama (AL-Kindy College Medical Journal, 2011)
BACKGROUND : Bifurcational coronary lesions arefrequent and amounts to almost one fifth of routinepractice concerning up to 15 – 20 % of cases .Revascularization by percutaneous coronaryintervention ( PCI ), of bifurcational lesion hasbecome easier by stenting yet it remains a frequentchallenge.OBJECTIVE : To evaluate the success and hospitalcomplications of two most frequent technique of stentdeployment in bifurcational PCI.METHODS : We prospectively analysed the data of140 consecutive patients with bifurcational PCI atIbn_Al-Bitar Hospital for cardiac surgery for theperiod from July 2008 to July 2009 .Depending on whether the side branch was stented ornot, the patient has fallen into two groups : -Group A; stenting of the main vessel and angioplastyof the branch.Group B; stenting of both main vessel and its branch .The early outcome of the bifurcational PCI and allcomplications during hospitalization that include;death, acute Myocardial infarction , emergencypercutaneous treatment and coronary artery bypassgraft (CABG) were evaluated in the studied groups.RESULTS : The studied sample consisted of 140patients,107(76.3%)were male and 33(23.7%) werefemale. Group A consisted of 90 patients (64.3%)while group B consisted of 50 patients(35.7%).Acuteprocedural success was (94.2%) in group A and (80%)in group B while hospital major adverse cardiacevent(MACE) were noted in 3.8% of group A and20% of group B,(PV=0.04)CONCLUSION: In bifurcational PCI stenting of theside branch has made no extra advantage in term ofprocedural success and early outcome.